Anesthetic Management of A Patient with Henoch-Schonlein Purpura for Caesarean Section - Wijaya, Indriyani (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: Henoch-Schonlein Purpura or Immunoglobulin-A vasculitis is a systemic vasculitis caused by immune complexes that attack small blood vessels. The classic symptoms of Henoch-Schonlein Purpura include erythema purpura, arthralgia, gastrointestinal complaints, and renal involvement. Some cases show that pregnancy itself could be the trigger for its recurrence and lead to early delivery. Case report: A 33-year-old patient, G2P1A0 and 35 weeks and 4 days pregnant complained of diarrhea 8 days before hospital admission (8-15 times per day). The patient was diagnosed with Henoch-Schonlein Purpura 3 years ago. Upon monitoring in the ward, the fetus was found to be in a compromised condition and an emergency cesarean section was needed. The patient was assessed as having an ASA II physical status and was anesthetized with regional anesthesia epidural in the sitting position, with a median approach, puncture at L3-L4 level, and with 12 ml of Bupivacaine 0.5% isobaric. Postoperative care was continued in the ward. As long as there are no contraindications, a neuraxial block could be performed on parturient patients with Henoch-Schonlein Purpura who would undergo a cesarean section. Neuraxial block, namely epidural block, has the added advantage of being a postoperative analgesic and helps to avoid the use of Non-Steroidal Anti Inflammatory Drugs (NSAIDs) in Henoch-Schonlein Purpura patients who often have renal complications. Conclusion: Caesarean Section with Henoch-Schonlein Purpura disease has been reported with Epidural Block Anesthesia without complications.